2010
DOI: 10.1002/dvg.20651
|View full text |Cite
|
Sign up to set email alerts
|

Generation of mice with a conditional null allele for Wntless

Abstract: Summary The Wnt-signaling pathway is necessary in a variety of developmental processes and has been implicated in numerous pathologies. Wntless (Wls) binds to Wnt proteins and facilitates Wnt sorting and secretion. Conventional deletion of Wls results in early fetal lethality due to defects in body axis establishment. To gain insight into the function of Wls in later stages of development, we have generated a conditional null allele. Homozygous germline deletion of Wls confirmed prenatal lethality and failure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
177
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(181 citation statements)
references
References 27 publications
4
177
0
Order By: Relevance
“…Similar to β‐catenin‐LKO and LRP5‐6‐LDKO, we observed a significantly lower liver weight to body weight ratio in EC‐Wls‐KO6, 7, 14 (Fig. 2A).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…Similar to β‐catenin‐LKO and LRP5‐6‐LDKO, we observed a significantly lower liver weight to body weight ratio in EC‐Wls‐KO6, 7, 14 (Fig. 2A).…”
Section: Resultssupporting
confidence: 68%
“…Mice were fed regular chow in standard caging and kept under a 12‐hour light–dark cycle with no enrichment. Lyve1‐cre mice were purchased from Jackson Laboratories15 and bred with Wls flox/flox mice 7, 14. Lyve1‐cre +/– ;Wls flox/flox are hereafter referred to as EC‐Wls‐KO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Its loss prevents Wnt secretion and hence is a way to generate the Wntless phenotype. 9 Previously, use of liver-specific Wls-LKO allowed us to study any role of hepatic epithelial cellederived Wnt proteins in initiation of LR and metabolic zonation. 10 Interestingly, continued examination of b-catenin signaling, cyclin-D1 expression, and markers of S phase in the Wls-LKO mice revealed a prolonged hepatocyte proliferative program, suggesting that hepatocytes may be the source of at least some termination signal for b-catenin signaling at the time when its activation or hepatocyte proliferation is not deemed necessary anymore.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in another study, Wan et al (38) observed a lower bone mass in the postnatal Col1a1-Cre;Wls CKO mutants. It should be noted that all three studies used different Wls CKO mouse models: the Maruyama et al (55) study used Wls ex2 CKO (56), Wan et al (38) used Wls ex3 CKO (57), and we used Wls ex1 CKO, in which the ATG start site was also floxed, generated by a third group (52). In view of the discrepancies among the findings, it is important to resolve any differences arising from using different mouse models to ensure that the results are truly biologically relevant.…”
Section: The Use Of Different Wntless Conditional Knockout Mouse Modementioning
confidence: 99%